Differences in catching time and baits on the catch results of Krendet in Coastal Fishing Port (CFP) Sadeng, Gunungkidul, Yogyakarta - Riris Amaylia Putri; Agus Suherman; Bogi Budi Jayanto (Depik, 2022)
Krendet is one of the fishing gears used to catch Lobster in the South Coast of Java. Krendet is a passive fishing gear. Lobster is a fishery commodity that has high economic value. This research was conducted to determine the difference in lobster catches based on differences in fishing time and bait types on Krendet fishing gear. The method used in this research is experimental fishing with 4 treatment combinations and 6 repetitions. The difference in fishing time used was morning – afternoon and afternoon – morning, while the bait used was trash fish and no bait as a control. This research was carried out in February 2021 in the waters around the Sadeng area, Gunung Kidul. The analysis carried out in this study used the Two Way Anova Test method. The results showed that the time difference had an effect on the number of catches. The effective time to catch Lobster is at night. This can be caused by Lobster's behavior or habits which tend to be active at night. Giving bait to Krendet is also able to increase the number of catches. The trash fish bait is able to lure the Lobster to come closer to Krendet. Giving bait to Krendet is also able to increase the number of catches. The trash fish bait is able to lure the Lobster to come closer to Krendet so that the Lobster can be trapped.Keywords:KrendetLobsterCoastal Fishing PortSadeng